Joan of Arc - Boutet de Monvel, Louis-Maurice, 1851-1913 (A Studio book, 1980)
A biography of the peasant girl who led the French army to victory against the English and paved the way for the coronation of King Charles VII. This is a facsimile of the original 1896 French edition.